The Campaigns Against Drug Abuse Cases at Barangay Ugong Valenzuela City: Vol. 3, No. 1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researcher conducted a study to determine the efforts and processes for conducting campaigns against drug abuse cases in Barangay Ugong, Valenzuela City. The three groups of respondents were selected using purposive sampling techniques based on the survey questionnaire results.The study used descriptive research to describe the population's characteristics. Non-experimental research was used. The researcher interviewed Badac personnel, force multipliers, and PNP. The main instruments used to gather information to answer the specific problem raised were the questionnaire, unstructured interview, and group discussion. The study found that Badac personnel were much more knowledgeable about conducting campaigns against drug abuse cases than the force multipliers and PNP. The respondents assessed problems relating to drug abuse as "serious." Measures proposed relating to campaigns against drug abuse were interpreted as "highly recommended." The study revealed that the campaign does not significantly impact drug abuse cases. However, Barangay Ugong can improve the campaign's performance by engaging the aid of respondents based on the survey results. In addition, the Badac personnel, force multipliers, and PNP all have the same effectiveness result. Thus, the study recommended that the campaign be administered effectively to ensure that the campaign against drug abuse cases continues to develop.